Oral manifestations of COVID‐19 and its management in pediatric patients: A systematic review and practical guideline - Kamyar Nasiri; Sahar Tehrani; Meysam Mohammadikhah; Morteza Banakar; Mojgan Alaeddini; Shahroo Etemad‐Moghadam; Gustavo V. O. Fernandes; Artak Heboyan; Shima Imannezhad; Farid Abbasi (Clinical and Experimental Dental Research, 2023)
Abstract Objectives The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) virus causes coronavirus disease 2019 (COVID‐19), a respiratory infection that has spread worldwide and is responsible for a high death toll. Although respiratory symptoms are the most common, there is growing evidence that oral signs of COVID‐19 can also be seen in children. The purpose of this systematic review is to provide a comprehensive analysis of the available data on the oral manifestations of COVID‐19 in children and to recommend appropriate methods of diagnosis and treatment. Methods A systematic search of the MEDLINE, EMBASE, Scopus, and Web of Science databases was done to discover relevant papers published between their establishment and January 2023. Articles detailing oral symptoms in pediatric patients with confirmed COVID‐19 infection were included, and data on clinical characteristics, diagnosis, treatment, and outcomes were extracted and evaluated. Results A total of 24 studies involving 2112 pediatric patients with COVID‐19 were included in the review. The most common presentations are oral lesions, taste and smell disorders, oral candidiasis, hemorrhagic crust, tongue discoloration, lip and tongue fissuring, gingivitis, and salivary gland inflammation. These manifestations were sometimes associated with multi‐system inflammatory syndrome in children (MIS‐C) or Kawasaki disease (KD). Management strategies varied depending on the severity of the oral manifestation and ranged from symptomatic relief with topical analgesics to systemic medications. Conclusion Oral symptoms of COVID‐19 are relatively prevalent in juvenile patients and can be accompanied by severe systemic diseases, such as MIS‐C or Kawasaki illness. Early detection and adequate care of these oral symptoms are critical for the best patient results. Understanding the underlying pathophysiology and developing targeted treatments requires more investigation.